The influence of sintering temperature on mechanical and microstructural properties of bovine hydroxyapatite - (:unkn) unknown (Trans Tech Publications Ltd, 2005)
The influence of sintering temperature on densification, microstructure and the mechanical properties of bovine hydroxyapatite (BHA), produced by a calcination method, was investigated. Densification and mechanical properties increased over increasing sintering temperature in the range between 1000°C and 1300°C, and there are evidences of optimum sintering temperature at 1200°C. The measured mechanical properties indicate sintered BHA-bodies as interesting biomaterials for further investigation in biomedical applications.
Keywords: Bovine hydroxyapatite; Mechanical properties; Microstructure; Sintering